Understanding and Improving Morbidity and Mortality after Hip Fracture - Chaudhry, Harman (My University, 2016)
Hip fractures are common injuries with devastating consequences, including high rates of morbidity and mortality. The purpose of my thesis was to lay the foundation for further research which can fully explore: i) the epidemiology of morbidity and mortality following hip fracture; ii) risk factors for poor outcomes following hip fracture; iii) causes and pathways to mortality following hip fracture; iv) secondary prevention of morbidity and mortality following hip fracture; and v) potential interventions to improve outcomes following hip fracture. To this end, I will first detail the design, execution, results, and ‘lessons learned’ of a prospective observational pilot cohort study that recruited 100 consecutive patients aged ≥18 years presenting with a hip fracture to the Juravinski Hospital and Cancer Centre of the Hamilton Health Sciences. The primary aim of this pilot study was to assess the feasibility of a larger prospective international cohort study. Second, I will present a systematic review and meta-analysis of a promising intervention that consisted of multi-disciplinary (specifically geriatrician-led) co-management of hip fracture patients. This intervention has previously been shown to reduce mortality and length of stay following hip fracture. The meta-analysis presented will determine the effectiveness of this intervention in reducing the incidence, duration, and severity of delirium—a common condition following hip fracture.
Keywords: Hip Fracture; Observational Study; Systematic Review; Morbidity and Mortality